Mapping flooded risk area in East Java Indonesia using remote sensing data. Issue 1 (February 2021) - Cahyono, B E; Cahyatri, P; Purwandari, E; Misto; Febrianti, N
Abstract: Flooded risk area describes the potential ease of an area to experiencing flooding. Several natural factors such as intensity, duration, and distribution of rainfall, land use / land cover, slope of the area, and soil type can affect the risk of flooding. This study aims to create the flooding risk map level of an area. Those parameters which affect the risk level are classified to be marked and weighted. The equation called Kingma algorithm is then applied to the weighted parameters to get the risk level value. The results are then classified and mapped into 3 classes of risk level that are safe, risky, and highly risk. This study showed that the highly risk areas are located in the flat area, low infiltration soil, and high intensity of rainfall. In contrast, the steep slope areas with high infiltration level of soil and still have a lot of vegetation growing.